Preschoolers’ cognitive flexibility and emotion understanding: a developmental perspective - Mengxia, Li (Frontiers in Psychology, 2024)
Cognitive flexibility is the ability to adapt to changing tasks or problems, while emotion understanding is the ability to interpret emotional cues and information in different contexts. Both abilities are crucial for preschoolers’ socialization. This study selected 532 preschool children aged 3-6 years from two kindergartens in a central province of China. The Dimensional Change Card Sorting (DCCS) task and emotion understanding tasks were used to investigate the developmental characteristics of cognitive flexibility, emotion understanding abilities, and their relationship. The results showed: 1) For cognitive flexibility, children older than 5 years scored significantly higher than younger children, and girls scored higher than boys. 2) For facial emotion recognition: i) Children’s recognition scores for happy, sad, and angry expressions were significantly higher than fear; children could accurately recognize happy, sad, and angry emotions by age 3, while fear recognition developed rapidly after age 5; ii) Girls scored higher in recognizing fearful faces than boys. 3) For situational emotion understanding: i) Children’s development followed the hierarchical order of external, desire, clue, and belief-based understanding. Situational and desire-based understanding already reached high levels by age 3, while clue and belief-based understanding developed quickly after age 5; ii) Girls scored higher than boys in belief-based emotion understanding. 4) Cognitive flexibility significantly predicted children’s facial emotion recognition, external and desire-based emotion understanding. Parents and teachers should cultivate children’s cognitive flexibility and provide personalized support. They should also fully grasp the characteristics of children’s emotion understanding development, systematically nurture their emotion understanding abilities, and leverage cognitive flexibility training to improve their emotion understanding.